Digital Financial Decisions: Evidence on Social Influence, Technology, and Herd Behavior in Emerging Financial Ecosystems - Halimatus Sakdiyah; Ira Yudistira; Imam Wahyudi (InFestasi, 2026)
The rapid growth of digital financial ecosystems has transformed how individuals make investment and consumption decisions within socially connected and technology-driven environments. This study examines the influence of psychological, social, and technological factors on herd behavior and digital investment decisions, as well as their implications for perceived market impact. Using a quantitative approach, data were collected from 105 active users of digital financial platforms in East Java, Indonesia, including cryptocurrency investors, paylater users, and digital investment application users. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that social and technological factors positively and significantly influence investment and consumption decisions, while psychological factors significantly affect herd behavior but do not directly influence investment decisions. Herd behavior also does not significantly moderate the relationships between psychological, social, and technological factors and investment decisions. Furthermore, investment and consumption decisions significantly contribute to perceived market impact. These findings indicate that digital financial behavior is increasingly shaped by social interaction and technological facilitation rather than solely by internal psychological mechanisms. This study contributes to behavioral finance literature by extending herd behavior analysis into digitally mediated financial environments.